Acceptance of Traditional Chinese Medicine in the Neonatal Intensive Care Unit: A Launching Point - Julie Johnson Rolfes MD; Kimberly Christensen MOM, DipIOM, LAc; Lynn A Gershan MD, CM (SAGE Publishing, 2020)
Background Because neonatology is a relatively new medical specialty, it is host to on-going, rapid adaptation and evolution of medical treatments and practices. This process has almost exclusively focused on Western, biomedical treatment modalities, without inclusion of potentially beneficial Traditional Chinese Medicine practices. It is unclear how receptive health-care providers in the neonatal intensive care unit (NICU) and families of NICU patients would be to the introduction of adapted Traditional Chinese Medicine treatments into the NICU environment. Objective To assess the potential for engagement of patients, families, and staff in the NICU with Traditional Chinese Medicine therapies and to provide targeted education and low-risk Traditional Chinese Medicine treatments to support the health and well-being of those 3 groups. Methods A feasibility pilot study including weekly walk-in Traditional Chinese Medicine sessions within the NICU for parents and staff, and neonatal patient consultations, both of which included hands-on therapies and education tailored to each participant's unique needs. Pre- and postsurveys were administered over 3 phases. Results Walk-in sessions were attended by 83 adults and participants reported benefits, with no ill effects. There were 5 neonatal consultations with staff expressing an interest in more. Several obstacles to accessing Traditional Chinese Medicine modalities were identified in pre-surveys and were addressed with education and preemptive modifications to the therapies offered. Conclusion Acceptance of Traditional Chinese Medicine modalities in the NICU opens the door to future studies implementing integrative health services into the NICU care model.